2006
DOI: 10.1529/biophysj.106.085027
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Composition Dependence of the Interaction of δ-Lysin with Ternary Mixtures of Sphingomyelin/Cholesterol/POPC

Abstract: The kinetics of carboxyfluorescein efflux induced by the amphipathic peptide delta-lysin from vesicles of porcine brain sphingomyelin (BSM), 1-palmitoyl-2-oleoyl-phosphatidylcholine (POPC), and cholesterol (Chol) were investigated as a function of temperature and composition. Sphingomyelin (SM)/Chol mixtures form a liquid-ordered (L(o)) phase whereas POPC exists in the liquid-disordered (L(d)) phase at ambient temperature. delta-Lysin binds strongly to L(d) and poorly to L(o) phase. In BSM/Chol/POPC vesicles t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
144
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(154 citation statements)
references
References 75 publications
(127 reference statements)
6
144
1
3
Order By: Relevance
“…When purifi ed AChR or ␥ M4 was included in different lipid:protein ratios in the reconstituted system, no significant effects were apparent on the lipid composition of DRM and DSM fractions, suggesting that lipid composition is independent of protein content. Recent studies using lipid vesicles having the same composition as in the present study (Chol/SM/POPC) reported the occurrence of ( l d + l o ) domain coexistence ( 70,71 ) or only one type of domain ( 72 ). It is interesting to compare the DRM and DSM lipid compositions obtained from the different liposomes studied ( Fig.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…When purifi ed AChR or ␥ M4 was included in different lipid:protein ratios in the reconstituted system, no significant effects were apparent on the lipid composition of DRM and DSM fractions, suggesting that lipid composition is independent of protein content. Recent studies using lipid vesicles having the same composition as in the present study (Chol/SM/POPC) reported the occurrence of ( l d + l o ) domain coexistence ( 70,71 ) or only one type of domain ( 72 ). It is interesting to compare the DRM and DSM lipid compositions obtained from the different liposomes studied ( Fig.…”
Section: Discussionmentioning
confidence: 60%
“…It is interesting to compare the DRM and DSM lipid compositions obtained from the different liposomes studied ( Fig. 3A ) with the phase diagram postulated by Pokorny et al ( 70 ) ( Fig. 6 ), bearing in mind that detergent extraction at 4°C results in the formation of a quaternary phase system.…”
Section: Discussionmentioning
confidence: 80%
“…Our data indicates that apoA-I solubilizes a more homogeneous bilayer which is consistent with the formation of condensed cholesterol/phospholipid complexes whose stoichiometry increases with the cholesterol concentration. However, in the ternary system of phosphatidylcholine/ sphingomyelin/cholesterol, where lateral fluid-fluid phase separation into phospholipid-rich l d and sphingomyelin/cholesterol-rich l o domains has been demonstrated, apoA-I preferentially solubilizes cholesterol-poor l d domains [21,52]. In our model (Step 1), the hydrophobic Cterminal α-helices of apoA-I insert into lattice defects in the membrane surface which occurs when DMPC bilayers undergo a thermal phase transition ( Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, membranes composed of POPC, which forms zwitterionic bilayers with liquid disordered phase properties at 25°C, along with model membranes of increased complexity, including POPC/POPG (80:20 molar ratio) and POPC/Chol/SM (27:33:40), were included. At 25°C, POPC/Chol/SM (27:33:40) membranes are in a homogeneous liquid-ordered phase (42). Phospholipids with a PG headgroup are negatively charged and were included to evaluate the effects of charge.…”
Section: Cyclotide-membrane Binding Affinity Is Dependent On Lipidmentioning
confidence: 99%